Analysis of the Health Assessment of Bank Tabungan Negara (BTN) Using the RGEC Approach (Risk Profile, Good Corporate Governance, Earnings, Capital - Suharini; Ratih Hastasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bank health must be maintained and/or improved so that public trust in banks is always maintained. The size of the bank's assessment has been determined by Bank Indonesia, so that the bank is required to make regular or periodical reports on all of its activities. This research is a descriptive study with quantitative data types that aim to determine the level of soundness of the Bank using the RGEC approach (Risk Profile, Good Corporate Governance, Earnings, Capital). The indicators used to measure the soundness of banks in this study are: NPL, LDR, GCG, ROA, ROE, BOPO and NIM. This indicator refers to Bank Indonesia Circular No. 6/23/DPNP of 2004 and Bank Indonesia Circular No. 15/15/DPNP of 2013. The results showed that several indicator ratio values ​​that had been accumulated became composite rating values ​​(PK), there was an increase in composite values ​​from 62.9% PK(3) in 2019, to 80% (PK 2 ) in 2020 and 82.85% (PK 2) in 2021. So that Bank BTN in 2019 in the